Nanoclay Reinforced Polymer Composites Natural Fibre/Nanoclay Hybrid Composites - Jawaid, Mohammad; Qaiss, Abou el Kacem; Bouhfid, Rachid (Engineering Materials,, 2016)
This book highlights the most essential advances in nanoclay-based nanocomposites, especially natural fibre-reinforced polymer composites. Readers will find extensive information on nanoclay from preparation to applications, and the characterization techniques needed in order to evaluate the resulting properties of nanoclay-based natural fibre-reinforced polymer composites. Topics covered include the characterization of nano-sized clay, chemical modification, and processing techniques for nanocomposites from nanoclay. The book offers a valuable reference guide for academics and industrial practitioners alike.